The Influence of Organizational Culture and Leadership Roles on Knowledge Sharing at PT. Thriveni - Akta Dia Nauly; Hamid Halin; Shafiera Lazuarni (ProBisnis : Jurnal Manajemen, 2023)
This study aims to analyze the influence of organizational culture and the role of leadership on knowledge sharing at PT. Develop. This study uses a questionnaire as a tool in collecting basic data. This research was conducted at PT. Thriveni with a total of 54 respondents. Methods of data collection through questionnaires and analyzed using multiple linear regression. The results of the investigation show that partially Organizational Culture has a positive and significant effect on Knowledge Sharing. The Role of Leadership has a positive effect on Knowledge Sharing. Simultaneously, Organizational Culture and Leadership Role have a positive and significant effect on Knowledge Sharing.